Translation, cultural adaptation and validation for Brazilian Portuguese of the Cardiff Acne Disability Index instrument - Luciana Rosa Grando; Roberta Horn; Vivian Trein Cunha; Tania Ferreira Cestari (Sociedade Brasileira de Dermatologia, 2016)
Abstract BACKGROUND: The Cardiff Acne Disability Index was originally developed in English for measuring quality of life of acne patients. Considering the psychosocial impact of this disease, it is important to have instruments culturally and linguistically validated for use in Brazilian adolescents. OBJECTIVE: To translate the Cardiff Acne Disability Index into Brazilian Portuguese, culturally adapt it, and verify its reliability and validity in adolescent patients with acne. METHODS: In the first step, the Cardiff Acne Disability Index was translated and validated linguistically to Brazilian Portuguese in accordance with international guidelines published. In the second step, the validation of the Cardiff Acne Disability Index into Brazilian Portuguese instrument was performed, when patients aged from 12 to 20 years with acne were selected. The participants were interviewed to collect demographic data, submitted to the classification of acne by the Global Acne Grading System and invited to respond the Cardiff Acne Disability Index into Brazilian Portuguese version and DLQI (>16 years) or CDLQI (≤16 years). The internal consistency of Cardiff Acne Disability Index into Brazilian Portuguese was assessed by Cronbach's alpha coefficient and concurrent validity was measured by the Spearman correlation coefficient and Student 's t-test for paired samples. RESULTS: The study included 100 adolescents. The Cardiff Acne Disability Index into Brazilian Portuguese version showed good reliability and internal consistency (Cronbach's alpha = 0.73). The concurrent validity of the scale was supported by a strong and significant correlation with CDLQI / DLQI instruments (rs=0.802;p<0.001). CONCLUSIONS: Cardiff Acne Disability Index into Brazilian Portuguese version is a reliable, valid and valuable tool to measure the impact of acne on quality of life in adolescent patients.